STUDI TENTANG PEMBINAAN AKHLAK PADA PESERTA DIDIK MELALUI KEGIATAN EKSTRAKURIKULER DI SMA NEGERI 1 LEMONG TAHUN PELAJARAN 2025/2026 - NINING FEBRIYANTI (UNISAN JURNAL, 2025)
This study aims to understand the moral development of students through extracurricular activities at SMA Negeri 1 Lemong in the 2025/2026 academic year. The primary issue examined is how non-academic activities contribute to the development of moral, religious, discipline, and responsibility values ​​in students. This research uses a qualitative case study approach, focusing on a contextual and in-depth understanding of moral development practices within the school environment. Data were collected through semi-structured interviews, participant observation, and documentation. Participants included the principal, extracurricular teachers, and students active in Islamic Spirituality (Rohis), Scouting, sports, and social activities. The results indicate that moral development occurs through three main mechanisms: (1) internalization of religious and moral values ​​through Islamic Spirituality activities, (2) the development of discipline and responsibility through Scouting and sports activities, and (3) strengthening empathy and social solidarity through social action and cross-class activities. The role of the mentor as a moral role model and value facilitator is a key factor in the success of this process. These findings strengthen the theory of experiential moral education and provide empirical evidence that extracurricular activities can serve as an effective vehicle for contextual and sustainable character development. This research has implications for the development of educational policies that prioritize extracurricular activities as a strategic instrument for character development in secondary schools. Further research using a longitudinal approach is recommended to explore the long-term impact of these activities on students' moral behavior.